Dynamics and morphology of droplet penetrating a soap film. (25th February 2022) - Wei, Yanju; Mu, Zhiqiang; Zhang, Yajie; Yang, Yajing; Liu, Shenghua; Law, Chung K.; Saha, Abhishek
Abstract: Abstract : This work reports experimental observation and theoretical explanation of the dynamics and morphology of a droplet passing through a soap film. During the process, the film undergoes four sequential responses: (1) film deformation upon droplet impact; (2) drop–film detachment; (3) coalescence of the film shell with the drop; (4) peel-off of the film shell. Physical models and the corresponding analytical expressions are developed to reveal the underlying physics for the observed four responses. It is identified that the film is an elongated catenoid under continuous stretch by the droplet, and that they separate at the fixed height of 5.8 times of the droplet radius while the detach point is located at the centre of the height. After separation, the droplet is wrapped with a film shell, which is then punctured by the ring tip of the converging surface wave at the impacting Weber number range of [45, 225]. The film shell then coalesces with the droplet, falls off with a fixed velocity and is eventually ejected as a bubble leaving the droplet with a transplanted surface of the soap solution.